High-contrast computed tomographic angiography better detects residual intracranial arteriovenous malformations in long-term follow-up after radiotherapy than 1.5-tesla time-of-flight magnetic resonance angiography - Giesel, Frederik L.; Essig, Marco; Zabel-du Bois, Angelika; Bock, Michael; Tengg-Kobligk, Hendrik von; Afshar-Omarei, Ali; Debus, Jürgen; Kauczor, Hans-Ulrich; Krix, Martin (Acta radiologica, 2010)
Background: Computed tomography angiography (CTA) and magnetic resonance angiography (MRA) are noninvasive alternatives for therapy monitoring of cerebral arteriovenous malformation (AVM).Purpose: To evaluate if CTA is able to detect residual AVM in the long-term follow-up after radiotherapy when time-of-flight (TOF) MRA could no longer detect a remaining nidus.Material and Methods: 18 patients with intracranial AVM were included between November 2005 and August 2007 who were scheduled for CTA (16-slice CT, 1-mm slice thickness, 90 ml iomeprol 400 mg I/ml, 4 ml/s) in the follow-up of radiotherapy. In these patients, MRA (3D-TOF, and bolus tagging at 1.5T) could no longer detect a remaining nidus.Results: The previously performed MRA (median time between CTA and MRA, 2.5 months) described total obliterations in 14 and subtotal obliterations in two AVM cases. Two MRA diagnoses were inconclusive due to artifacts. CTA (median time after therapy, 28 months; range, 5?66 months) could provide a diagnosis in all cases, but confirmed the MRA diagnosis only in 50% of the cases. A residual nidus was shown in an additional six cases, and subtotal obliteration in another three cases. The interval between radiotherapy and the follow-up examination was significantly different (P<0.05) between false- and true-negative MRA examinations (median, 18 vs. 30 months).Conclusion: High-contrast CTA is a sensitive tool in the detection of AVM and is able to identify residual AVM after radiotherapy even if previously performed TOF MRA at 1.5T shows total obliteration.